The Effectiveness of Electronic Investigation Management as Supervision of Investigations to Improve the Professionalism of Madiun Police Reskrim Unit Investigators - Syahputra, Achmad Firman (Advances in Police Science Research Journal, 2024)
Electronic Managenement System has been implemented since 2019 which in its course has undergone many updates and evaluations. The purpose of this study is to describe the use of EMP Applications and find the effectiveness of using EMP in Madiun Police Station to supervise investigations to improve the professionalism of investigators.The research carried out uses the theory of effectiveness and uses concepts in the form of the Concept of Investigation Management, the Concept of Electronic Systems of Investigation Management, and the Concept of Professionalism. The method used is in the form of Qualitative Research Methods. After conducting research, it was found that the use of the EMP Application still experienced many tactical obstacles such as the internet and computers as sara and technical such as the ability of investigators to use this application. Then the application is also less actively used by investigators which has an impact on the absence of investigative supervision at the Madiun Police Criminal Investigation Unit, so that investigation supervision using the EMP Application has not been effectively implemented.